Type 2 diabetes mellitus in Peru: A literature review including studies at high-altitude settings. (December 2021) - Rocca, Jesus; Calderón, María; La Rosa, Alberto; Seclén, Segundo; Castillo, Oscar; Pajuelo, Jaime; Arbañil, Hugo; Medina, Félix; Garcia, Luis; Abuid, Juan
Abstract: We performed a comprehensive review of recent publications about type 2 diabetes mellitus (T2DM) in Peru, including studies among people living at high altitude above the sea level. An increase in the prevalence of T2DM in Peru has been reported, the reasons are multifactorial and coinciding with the strong economic growth that our country has experienced over the last 20 years along with migration from the Andean regions to the coast and the adoption of a lifestyle that is a known to be a risk factor for obesity and insulin resistance. Scarce information is available in Peru about the prevalence of chronic complications of T2DM such as retinopathy, neuropathy, and nephropathy. There is a need for a health care plan based on early diagnosis of T2DM to reduce social and economic problems, as recommended by the WHO and the United Nations.